A Escola Normal do Ceará nos Anos de 1930 a 1950: Palco de Debates Políticos e Pedagógicos no Calor das Reformas - Silva, Maria Goretti Lopes Pereira e (2009)
The subject of the present study is the Normal School of Ceará (Brazil), as the focal point in the framework of educational politics in this State, between 1930 and 1950, a period characterized by the outbreak of great debates around the current educational reforms. In this sense, it supports the thesis that the Normal School of that period served as the arena for political quarrels and disputes, particularly, at a local level, more so than a place for pedagogical debates. It is stated, furthermore, that the Normal School begins to loose its prestige and centrality around the years 1950. The study intended to understand the historical process of teacher preparation in the context of the Normal School in the above mentioned period. The daily newspaper was selected as the main tool of data collecting, along with official documents and bibliographical reviews focusing upon the subject. The study was based upon the theoretical perspective represented by the New History approach associated to the comprehensive and historical research methods. Categories such as modernity, intellectual, conservativeness, as well as the emergence of a Brazilian curriculum under the influence of foreign studies were also taken into account in the data analysis process. The study results confirm that within the meanders of the consolidation of a teacher preparation project, the Normal School played an essential role in the field of contentions involving political groups and factions, which, if not ideologically divergent or contradictory, positioned themselves at opposed sides on the grounds of the political power. And, yet, the teacher preparation experience in the State of Ceará followed the same path as did the majority of Brazilian Normal Schools, connecting themselves to the most advanced pedagogical studies produced so far in the world, and for this accomplishment, the role of the native intellectuals was, in truth, outstanding. Moreover, it should be stressed that the Normal School as an institution immersed in the realm of a certain historical time, served the needs of that time. For, if in the years 1920, it should be put to use as a laboratory of new pedagogical ideas, in the years 1930, at least in a formal sense, it was to be held accountable for the formation of the new man required by a society, which was, at the same time, modern and conservative